Professional Needs of the Workplace - A Vital Component in Professional Curriculum - Sharma, Jaideep (Journal of Information and Knowledge, 2002)
The curricula of library and information science education at various levels should support the needs of the profession such requirement of the profession are properly understood by the activity analyssis of the professionals in their workplace.